Architecting Hierarchical WO3 Agglomerates Assembled With Straight and Parallel Aligned Nanoribbons Enabling High Capacity and Robust Stability of Lithium Storage - Dong, Xiaotong; Liu, Yongshuai; Zhu, Shikai; Ou, Yike; Zhang, Xiaoyu; Lan, Wenhao; Guo, Haotian; Zhang, Cunliang; Liu, Zhaoguo; Ju, Shuai; Miao, Yuan; Zhang, Yongcheng; et al. (Frontiers in Chemistry, 2022)
The pursuit of electrochemical energy storage has led to a pressing need on materials with high capacities and energy densities; however, further progress is plagued by the restrictive capacity (372 mAh g−1) of conventional graphite materials. Tungsten trioxide (WO3)-based anodes feature high theoretical capacity (693 mAh g−1), suitable potential, and affordable cost, arousing ever-increasing attention and intense efforts. Nonetheless, developing high-performance WO3 electrodes that accommodate lithium ions remains a daunting challenge on account of sluggish kinetics characteristics and large volume strain. Herein, the well-designed hierarchical WO3 agglomerates assembled with straight and parallel aligned nanoribbons are fabricated and evaluated as an anode of lithium-ion batteries (LIBs), which exhibits an ultra-high capacity and excellent rate capability. At a current density of 1,000 mA g−1, a reversible capacity as high as 522.7 mAh g−1 can be maintained after 800 cycles, corresponding to a high capacity retention of ∼80%, demonstrating an exceptional long-durability cyclic performance. Furthermore, the mechanistic studies on the lithium storage processes of WO3 are probed, providing a foundation for further optimizations and rational designs. These results indicate that the well-designed hierarchical WO3 agglomerates display great potential for applications in the field of high-performance LIBs.